Analysis of the Effectiveness of Communication Media in Teaching and Learning Activities of Teachers and Students at SD Negeri Cempaka Putih Barat 01 Post Covid-19 Pandemic (Zoom Meeting Case Study) - Wahyudi, Oki; Yulianto, Yulianto; Astuti, Maharnani Tri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The COVID-19 pandemic has brought significant changes to education, including the shift from face-to-face to online learning methods. Distance learning implemented during the pandemic is the main solution to ensure the continuity of the teaching-learning process while maintaining the safety and health of students and teaching staff. This study aims to analyze the effectiveness of using Zoom Meeting as a communication medium in teaching and learning activities at SD Negeri Cempaka Putih Barat 01 after the COVID-19 pandemic. The results show that Zoom Meeting provides several advantages as an alternative such as flexibility of time and place, as well as the ability to record learning sessions. However, this study also found various obstacles or barriers such as technical problems, limited internet access, and lack of direct social interaction and funding constraints and device limitations.